2016
DOI: 10.1186/s11671-016-1669-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of Novel Biocomposite Scaffold of Chitosan-Gelatin/Nanohydroxyapatite for Potential Bone Tissue Engineering Applications

Abstract: In this study, a three-dimensional chitosan-gelatin/nanohydroxyapatite (ChG/nHaP) scaffold was successfully fabricated and characterized in terms of swelling, degradation, cell proliferation, cell attachment, and mineralization characterizations. The ChG/nHaP scaffold was fabricated with a mean pore size of 100–180 μm. Our results showed that the physicochemical and biological properties of the scaffolds were affected by the presence of HaP. The swelling and degradation characteristics of the ChG scaffold were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 18 publications
2
31
0
Order By: Relevance
“…Chitosan is a cationic polysaccharide capable of interacting with the surface anions and connecting the cell to the surface . Several studies have shown that Cs effective being in cell adhesion, its effect is, however, weaker than gel . Nano‐Hydroxyapatite is a bioceramic compound that comprises the natural mineral component of the bone.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Chitosan is a cationic polysaccharide capable of interacting with the surface anions and connecting the cell to the surface . Several studies have shown that Cs effective being in cell adhesion, its effect is, however, weaker than gel . Nano‐Hydroxyapatite is a bioceramic compound that comprises the natural mineral component of the bone.…”
Section: Discussionmentioning
confidence: 99%
“…Nano‐Hydroxyapatite is a bioceramic compound that comprises the natural mineral component of the bone. Its presence in scaffold, not only produces chemical stimuli which remarkably enhance the physical attachments of cells, but also creates surface roughness for further stimulation cell‐surface adhesion . It is interesting to note that the shape of the nHA, whether spherical or slender, has significant impact on proliferation and osteogenic differentiation of stem cells …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, HA played an important role in improving the biological performance of the scaffold. Therefore, the ChG/nHA scaffold could be applied as a good candidate material for bone tissue engineering in regenerative medicine applications (Dan et al, ).…”
Section: Nanofibrous Fabrication Methodsmentioning
confidence: 99%